2018
DOI: 10.1039/c8nj02985g
|View full text |Cite
|
Sign up to set email alerts
|

Dual photoluminescence and charge transport in an alkoxy biphenyl benzoate ferroelectric liquid crystalline–graphene oxide composite

Abstract: GO has been dispersed in a ferroelectric liquid crystalline material to prepare a FLC–GO composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…The uniformity of POM color in the entire bright state has also confirmed that the LC molecules are uniformly aligned in the nematic matrix of the E7 LC [37][38][39][40][41]. However, the dispersion of MWCNTs in the E7 LC into different concentrations leads to the change in color of POMs, which is associated to the change in refractive index and/or birefringence (∆n) as reported previously [42][43][44]. Besides, all the POM images have also been processed by ImageJ software to analyze the uniformity of color within a POM image.…”
Section: Resultssupporting
confidence: 81%
“…The uniformity of POM color in the entire bright state has also confirmed that the LC molecules are uniformly aligned in the nematic matrix of the E7 LC [37][38][39][40][41]. However, the dispersion of MWCNTs in the E7 LC into different concentrations leads to the change in color of POMs, which is associated to the change in refractive index and/or birefringence (∆n) as reported previously [42][43][44]. Besides, all the POM images have also been processed by ImageJ software to analyze the uniformity of color within a POM image.…”
Section: Resultssupporting
confidence: 81%
“…Additionally, we have previously reported that the 2D-GO flakes exhibit two ab-sorption peaks at 230 and 300 nm,(supplementary figure S1), attributed to π-π* transitions of C=C bonds and to n-π* transitions of C=O bonds, respectively [19,26]. In 8CB/2D-GO composites, the successive addition of increasing weight concentration of GO results a trivial narrowing in the absorption bandwidth.…”
Section: Uv-visible Absorption Studymentioning
confidence: 93%
“…2D-GO nanoflakes were synthesized from commercially available graphite following the Hummers method as previously described in our previous articles [18,19,23]. We have utilized the same 2D-GO nanoflakes in this study which is already reported in our previous articles [19,23]. To prepare GO suspension in DMF, 0.65 mg of 2D-GO nanoflakes were dissolved in 160 microliter of DMF and sonicated for 2.5 hours.…”
Section: Dopant Material: Graphene Oxide Nanoflakesmentioning
confidence: 99%
See 2 more Smart Citations